Infrared radiation SiO2 (at) AlPO4 material as well as preparation method and application thereof

By synthesizing SiO2@AlPO4 material via a hydrothermal method, the problems of easy oxidation and complex preparation of existing radiation cooling materials have been solved. This method has resulted in infrared radiation materials with high reflectivity and emissivity, which can be used in cooling ceramics and have significant cooling effects and low cost advantages.

CN121107840APending Publication Date: 2025-12-12GUANGXI MONALISA NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511412531.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-29
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Existing methods for preparing radiation cooling materials are complex and costly, and the materials are easily oxidized, resulting in poor cooling performance and making it difficult to achieve long-term use.

Method used

SiO2@AlPO4 material was synthesized by hydrothermal method. Aluminum phosphate was coated with silica to form a high-temperature resistant infrared radiation material, which was used to prepare refrigeration ceramic blanks and improve the reflectivity and emissivity of the material.

Benefits of technology

It achieves structural stability at high temperatures, maintains high reflectivity and emissivity, has excellent cooling effect, significant cooling effect, and the preparation process is simple and low-cost, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121107840A_ABST
    Figure CN121107840A_ABST
Patent Text Reader

Abstract

The invention discloses an infrared radiation SiO2 (at) AlPO4 material as well as a preparation method and application thereof, and relates to the technical field of radiation refrigeration materials. The preparation method of the SiO2-coated AlPO4 material comprises the following steps: preparing aluminum phosphate; adding the aluminum phosphate into ethanol, and stirring and mixing to obtain a solution J; dropwise adding tetraethoxysilane into the alcohol-water system to obtain a solution K; and slowly adding the solution J into the solution K, adjusting the pH value to 8-10, magnetically stirring for 4-6 hours, centrifuging, washing, and drying at 80-120 DEG C for 2-8 hours, thereby obtaining the product. The SiO2-coated AlPO4 material disclosed by the invention has very strong high-temperature resistance and can be used for preparing a refrigeration ceramic blank, so that the ceramic has an excellent cooling effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of radiation cooling materials technology, and in particular to an infrared radiation SiO2@AlPO4 material, its preparation method and application. Background Technology

[0002] With societal progress, the demand for refrigeration equipment is increasing. However, most refrigeration equipment on the market requires external energy to operate, and some even have environmental impacts. Therefore, a new refrigeration method is urgently needed to improve this situation. Passive radiation refrigeration is a novel, energy-free, and environmentally friendly method that achieves cooling by reflecting as much sunlight as possible and emitting its own heat into outer space via infrared radiation. This requires the radiation refrigeration material to have extremely high reflectivity in the solar wavelength range and exceptional emissivity in the atmospheric window wavelength range to achieve its cooling effect.

[0003] Currently, research on radiative cooling mainly focuses on composite thin films and coatings. In 2019, Huang Xia successfully prepared MgHPO4·1.2H2O crystalline material via a hydrothermal method (X. Huang, N. Li, J. Wang, et al., “Single nanoporous MgHPO4·1.2H2O for daytime radiative cooling”). ACS Applied Materials Interfaces,2020,12(2):2252-2258, https: / / doi.org / 10.1021 / acsami.9b14615.) This material has a nanoporous structure, a reflectivity of 92.20%, and an emissivity of 94%. Cooling tests show that the MgHPO4·1.2H2O coating can achieve a daytime temperature about 5 ℃ lower than the ambient temperature. In 2023, Yan Kehui prepared a PVDF-HFP / Al2O3 flexible composite film using electrospinning (Yan Kehui, Preparation and Performance Study of Flexible Film for Daytime Radiation Cooling [D]. Shanghai: Donghua University, 2023.) The film has a solar reflectivity of 0.980 and an atmospheric window emissivity of 0.932. Under different conditions of sunny and cloudy days, the temperature drops by 4.6℃ and 2.1℃, respectively. However, although the above-mentioned materials have excellent radiation cooling performance, the preparation method of the materials is relatively complex and the manufacturing cost is relatively high, which makes the materials have certain practical limitations. Patent CN 111394069 A discloses a silica-coated magnesium phosphite radiative cooling material and its preparation method. This method uses magnesium phosphite and sodium silicate as raw materials to prepare the silica-coated magnesium phosphite radiative cooling material. Although this material has excellent cooling effect, magnesium phosphite is easily oxidized in an oxygen environment, making it difficult to use for extended periods. Aluminum phosphate is not easily oxidized, has a simple preparation method, and is inexpensive. It also possesses certain cooling properties and can be used as a cooling material. However, because ceramic preparation requires high firing temperatures, directly using aluminum phosphate to prepare refrigerable ceramic materials results in poor cooling performance. Summary of the Invention

[0004] To address the above shortcomings, this invention provides an infrared radiation SiO2@AlPO4 material, its preparation method, and its applications. This material exhibits strong high-temperature resistance and, when used to prepare refrigeration ceramic blanks, can enable ceramics to achieve excellent cooling effects. The specific technical solution is as follows: A method for preparing infrared radiation SiO2@AlPO4 material includes the following steps: (1) Preparation of aluminum phosphate; (2) Preparation of SiO2@AlPO4 material: Add aluminum phosphate to ethanol and stir for 2-4 h to obtain solution J, wherein the mass-volume ratio of aluminum phosphate to ethanol is (0.5-1) g: (20-30) mL; add tetraethyl orthosilicate dropwise to alcohol-water system to obtain solution K, wherein the volume ratio of tetraethyl orthosilicate to alcohol-water system is (1-4): (20-50); slowly add solution J to solution K, wherein the volume ratio of solution J to solution K is (20-30): (20-50), adjust pH to 8-10, stir magnetically for 4-6 h, centrifuge, wash, and dry at 80-120 ℃ for 2-8 h to obtain SiO2@AlPO4 material.

[0005] 2. The method for preparing an infrared radiation SiO2@AlPO4 material according to claim 1, characterized in that, in step (1), the method for preparing the aluminum phosphate is as follows: ① Mix aluminum acetate and deionized aluminum, adjust the pH to 4-7, and stir thoroughly at room temperature for 2-4 hours to prepare a 0.03-0.09 mol / L solution A; ② Add glutamic acid to solution A and stir at room temperature for 2-6 hours to obtain solution B; ③ Mix sodium tripolyphosphate and deionized water, and stir at 40~80 ℃ for 2~4 h to prepare a 0.1~0.2 mol / L C solution; ④ Add lysine to solution C and stir at room temperature for 2-6 hours to obtain solution D; mix solution B and solution D and stir thoroughly at room temperature for 4-6 hours to obtain solution E; ⑤ React the E solution at 120~180 ℃ for 12~24 h, cool to room temperature to obtain F; filter and wash the F to obtain G; dry the G at 80~100 ℃ for 2~4 h to obtain H; ⑥ Place the H in a rotary furnace, first heat it to 200-300 ℃ at a rate of 3-5 ℃ / min, hold it at that temperature for 0.5-1h, then heat it to 700-1200 ℃ at a rate of 5-10 ℃ / min, hold it at that temperature for 2-5h to obtain I, which is aluminum phosphate.

[0006] Preferably, in step ①, the pH is adjusted using hydrochloric acid with a mass concentration of 10~20wt%.

[0007] Preferably, in step ②, the molar ratio of glutamic acid to Al in solution B is (1~3):(1~3).

[0008] Preferably, in step ④, the molar ratio of lysine to sodium tripolyphosphate in solution D is (5~10):(1~3); and the molar ratio of Al to P in solution E is (1~1.3):(1~1.3).

[0009] Preferably, in step (2), the alcohol-water system consists of 5-15 ml of ethanol and 5-15 ml of deionized water.

[0010] Preferably, in step (2), the pH is adjusted using ammonia water with a volume concentration of 5% to 10%.

[0011] The present invention also provides a SiO2@AlPO4 material, which is prepared by the above preparation method.

[0012] This invention also provides an application of SiO2@AlPO4 material in the preparation of radiation-cooled ceramics, wherein the material is prepared by the above-described method.

[0013] Preferably, in the preparation of the radiation-cooled ceramic, the lower layer material, the middle layer material, and the upper layer material are placed in the lower layer, middle layer, and upper layer of the mold respectively, and then pressed into shape. The pressed blank is then placed in a muffle furnace and heated to 1200~1300 ℃ at a rate of 5-10 ℃ / min and held for 1~2 h to obtain the radiation-cooled ceramic. The mass ratio of the dry powder to the SiO2@AlPO4 material in the lower layer is (9~11):1; The mass ratio of the dry powder in the intermediate layer to the SiO2@AlPO4 material is (1~3):1; The mass ratio of the dry powder to the SiO2@AlPO4 material in the upper layer is (1~3):10; The dry powder is prepared by: placing 10-20% montmorillonite, 20-30% kaolinite, 30-50% talc, 5-15% sodium feldspar, and 5-15% potassium feldspar into a ball mill jar and ball milling for 1-2 hours to obtain the dry powder.

[0014] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention synthesizes SiO2@AlPO4 material using a hydrothermal method at a specific temperature. The high-temperature resistance of this material is enhanced by coating aluminum phosphate with silica, making its structure less susceptible to damage during high-temperature treatment or use at high temperatures, while maintaining high solar reflectivity and mid-infrared emissivity. The SiO2@AlPO4 material obtained by this invention is used to prepare ceramic tile blanks. After high-temperature firing (1200~1300 ℃), the blanks exhibit excellent cooling effects. Testing shows that the temperature of ceramic blanks containing SiO2@AlPO4 material is 3 ℃ lower than that of the original blanks without SiO2@AlPO4 material, approximately 1.5 ℃ lower than that of ceramic blanks containing aluminum phosphate without SiO2 coating, and approximately 7.5 ℃ lower than the ambient temperature.

[0015] 2. In the SiO2@AlPO4 material prepared by this invention, silicon dioxide exists in a spherical form, aluminum phosphate exists in a plate-like structure, and many protrusions appear on the surface of the particles. These tiny protrusions increase the multiple scattering phenomenon between particles, which increases the number of reflections of light on the surface and between particles, thereby improving the overall reflectivity. According to the test, the reflectivity of the SiO2@AlPO4 material of this invention can be as high as 94-97% in the solar band (0.3~2.5 µm) and the emissivity can be as high as 92-95% in the mid-infrared band (8~13 µm).

[0016] 3. The SiO2@AlPO4 material of this invention has a stable structure, is not easily oxidized or corroded, and its refrigeration effect does not change significantly with long-term use.

[0017] 4. The preparation process of the SiO2@AlPO4 material of this invention is simple, the reaction cycle is short, the raw materials are common, the cost is low, the controllability is strong, the target product can be prepared in large quantities, and it is easy to realize industrial production. Attached Figure Description

[0018] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below.

[0019] Figure 1 The image shows the XRD pattern of the SiO2@AlPO4 material prepared in Example 1. Figure 2 The image shows the microstructure of the SiO2@AlPO4 material prepared in Example 1. Figure 3 This is a comparison chart showing the cooling effect of the materials prepared in Example 1 and Comparative Example 1. Figure 4 The image shows a comparison of the cooling effects of the ceramic blank prepared in Example 1, the original ceramic blank without the SiO2@AlPO4 material of the present invention, and the ceramic blank prepared in Comparative Example 1. Detailed Implementation

[0020] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.

[0021] Example 1 ① Weigh a certain amount of aluminum acetate and deionized water, adjust the pH to 7 with 10 wt% hydrochloric acid, stir thoroughly at room temperature for 4 h to fully hydrolyze the aluminum acetate, and prepare a 0.03 mol / L solution A.

[0022] ② Add a certain amount of glutamic acid to A, stir at room temperature for 2 hours to mix thoroughly, and this mixture is called solution B; ensure that the molar ratio of glutamic acid to Al in solution B is 1:1.

[0023] ③ Weigh a certain amount of sodium tripolyphosphate and deionized water, stir at 40 ℃ for 4 h to fully dissolve them, and prepare a 0.1 mol / L C solution.

[0024] ④ Add a certain amount of lysine to C and stir at room temperature for 2 hours to mix thoroughly. This mixture is called solution D. Ensure that the molar ratio of lysine to sodium tripolyphosphate in solution D is 9:1. Mix solutions B and D and stir thoroughly at room temperature for 4 hours to mix thoroughly. This mixture is called solution E. Ensure that the molar ratio of Al to P in solution E is 1:1.

[0025] ⑤ Transfer E to a hydrothermal reactor (100 ml PTFE liner), place it in an oven and react at 180 °C for 12 h, then cool to room temperature to obtain F; filter F, then wash it three times each with deionized water and ethanol to obtain G; place G in a drying oven and dry at 100 °C for 2 h to obtain H.

[0026] ⑥ Place H in a rotary furnace and heat it to 200 ℃ at a rate of 3 ℃ / min, hold it at that temperature for 1 h, then heat it to 700 ℃ at a rate of 5 ℃ / min, hold it at that temperature for 5 h to obtain I, which is aluminum phosphate.

[0027] ⑦ Weigh 0.5 g of I and stir in 20 ml of ethanol for 2 h to obtain solution J; weigh 5 ml of ethanol and 15 ml of deionized water to form an alcohol-water system, and add 1 ml of tetraethyl orthosilicate to it to obtain K.

[0028] ⑧ Slowly add 20 mL of J to 20 mL of K, adjust the pH to 8 with 5% ammonia solution, and stir with a magnetic stirrer at 300 r / min for 6 hours at room temperature. This is called L.

[0029] ⑨L was centrifuged and washed three times with deionized water and ethanol to obtain M; M was placed in a drying oven and dried at 80 °C for 8 h to obtain N, which is SiO2@AlPO4 material.

[0030] In this embodiment, ceramic green bodies were prepared using SiO2@AlPO4 material: 20% montmorillonite, 20% kaolin, 30% talc, 15% sodium feldspar, and 15% potassium feldspar by mass ratio were weighed and placed in a ball mill jar, and ball milled for 1 h to prepare dry powder. A certain amount of dry powder and N were weighed and ball milled for 2 h to prepare green bodies, which were then pressed into shape. The dry powder and N were added in a gradient manner, with dry powder to N mass ratios of 11:1, 1:1, and 3:10, respectively, and placed in the lower, middle, and upper layers of the mold for pressing. The pressed green bodies were placed in a muffle furnace and heated to 1200 ℃ at a heating rate of 5 ℃ / min and held for 2 h, successfully preparing ceramic green bodies with radiative cooling properties.

[0031] Figure 1 The image shows the XRD pattern of the SiO2@AlPO4 material prepared in this embodiment. It can be seen from the image that the XRD pattern of the sample matches the standard cards for aluminum phosphate and silicon dioxide, indicating that the sample is composed of aluminum phosphate and silicon dioxide. The scanned image also shows that it is a SiO2@AlPO4 material.

[0032] Figure 2 The image shows the microstructure of the SiO2@AlPO4 material prepared in this embodiment. Figure 1 The data shows that silica exists in a spherical form, while aluminum phosphate exists in a sheet-like, rolled structure. Silica adheres to aluminum phosphate, and many protrusions appear on the particle surface. These tiny protrusions increase the multiple scattering phenomenon between particles, which increases the number of reflections of light on the surface and between particles, thereby improving the overall reflectivity.

[0033] Example 2: ① Weigh a certain amount of aluminum acetate and deionized water, adjust the pH to 6 using 13 wt% hydrochloric acid, and stir thoroughly at room temperature for 3 h to allow the aluminum acetate to be fully hydrolyzed, thus preparing a 0.05 mol / L solution A.

[0034] ② Add a certain amount of glutamic acid to A, stir at room temperature for 3 hours to mix thoroughly, and this mixture is called solution B; ensure that the molar ratio of glutamic acid to Al in solution B is 1:3.

[0035] ③ Weigh a certain amount of sodium tripolyphosphate and deionized water, stir at 50 ℃ for 3 h to fully dissolve them, and prepare a 0.2 mol / L C solution.

[0036] ④ Add a certain amount of lysine to C, stir at room temperature for 3 h to mix thoroughly, and this is called solution D; ensure that the molar ratio of lysine to sodium tripolyphosphate in solution D is 5:1; mix solutions B and D and stir thoroughly at room temperature for 5 h to mix thoroughly, and this is called solution E, ensuring that the molar ratio of Al to P in solution E is 1:1.3.

[0037] ⑤ Transfer E to a hydrothermal reactor (100 ml PTFE liner), place it in an oven and react at 160 °C for 16 h, then cool to room temperature to obtain F; filter F, then wash it three times each with deionized water and ethanol to obtain G; place G in a drying oven and dry at 90 °C for 2.5 h to obtain H.

[0038] ⑥ Place H in a rotary furnace and heat it to 220 ℃ at a rate of 4 ℃ / min, hold it at that temperature for 0.5 h, then heat it to 800 ℃ at a rate of 7 ℃ / min, hold it at that temperature for 4 h to obtain I, which is aluminum phosphate.

[0039] ⑦ Weigh 0.7 g of I and stir in 25 ml of ethanol for 3 h to obtain solution J; weigh 10 ml of ethanol and 10 ml of deionized water to form an alcohol-water system, and add 2 ml of tetraethyl orthosilicate to it to obtain K.

[0040] ⑧ Slowly add 30 mL of J to 50 mL of K, adjust the pH to 9 with 7% ammonia solution, and stir with a magnetic stirrer at 400 r / min for 5 hours at room temperature. This is called L.

[0041] ⑨L was centrifuged and washed three times with deionized water and ethanol to obtain M; M was placed in a drying oven and dried at 90 °C for 6 h to obtain N, which is SiO2@AlPO4 material.

[0042] In this embodiment, ceramic green bodies were prepared using SiO2@AlPO4 material: 10% montmorillonite, 20% kaolin, 50% talc, 10% sodium feldspar, and 10% potassium feldspar by mass ratio were weighed and placed in a ball mill jar, and ball milled for 2 hours to prepare dry powder. A certain amount of dry powder and N were weighed and ball milled for 1 hour to form a green body, which was then pressed into shape. The dry powder and N were added in a gradient manner, with the dry powder to N mass ratios of 10:1, 2:1, and 1.5:10, respectively, and placed in the lower, middle, and upper layers of the mold for pressing. The pressed green body was placed in a muffle furnace and heated to 1240 ℃ at a heating rate of 7 ℃ / min, and held for 2 hours, successfully preparing a ceramic green body with radiative cooling properties.

[0043] Example 3: ① Weigh a certain amount of aluminum acetate and deionized water, adjust the pH to 5 with 16 wt% hydrochloric acid, stir thoroughly at room temperature for 2.5 h to fully hydrolyze the aluminum acetate, and prepare a 0.07 mol / L solution A.

[0044] ② Add a certain amount of glutamic acid to A, stir at room temperature for 5 hours to mix thoroughly, and this mixture is called solution B; ensure that the molar ratio of glutamic acid to Al in solution B is 3:1.

[0045] ③ Weigh a certain amount of sodium tripolyphosphate and deionized water, stir at 70 ℃ for 2.5 h to fully dissolve them, and prepare a 0.15 mol / L C solution.

[0046] ④ Add a certain amount of lysine to C, stir at room temperature for 5 h to mix thoroughly, and this is called solution D; ensure that the molar ratio of lysine to sodium tripolyphosphate in solution D is 7:1; mix solutions B and D and stir thoroughly at room temperature for 5 h to mix thoroughly, and this is called solution E, ensuring that the molar ratio of Al to P in solution E is 1.3:1.

[0047] ⑤ Transfer E to a hydrothermal reactor (100 ml PTFE liner), place it in an oven and react at 140 °C for 20 h, then cool to room temperature to obtain F; filter F, then wash it three times each with deionized water and ethanol to obtain G; place G in a drying oven and dry at 85 °C for 3 h to obtain H.

[0048] ⑥ Place H in a rotary furnace and heat it to 260 ℃ at a rate of 5 ℃ / min, hold it at that temperature for 1 h, then heat it to 1000 ℃ at a rate of 8 ℃ / min, hold it at that temperature for 3 h to obtain I, which is aluminum phosphate.

[0049] ⑦ Weigh 0.9 g of I and stir in 27 ml of ethanol for 3.5 h to obtain solution J; weigh 15 ml of ethanol and 10 ml of deionized water to form an alcohol-water system, and add 3 ml of tetraethyl orthosilicate to it to obtain K.

[0050] ⑧ Slowly add 25 mL of J to 40 mL of K, adjust the pH to 10 with 8% ammonia solution, and stir with a magnetic stirrer at 500 r / min for 5 hours at room temperature. This is called L.

[0051] ⑨L was centrifuged and washed three times with deionized water and ethanol to obtain M; M was placed in a drying oven and dried at 100 °C for 4 h to obtain N, which is SiO2@AlPO4 material.

[0052] In this embodiment, ceramic green bodies were prepared using SiO2@AlPO4 material: 20% montmorillonite, 30% kaolin, 40% talc, 5% sodium feldspar, and 5% potassium feldspar by mass ratio were weighed and placed in a ball mill jar, and ball milled for 1 h to prepare dry powder. A certain amount of dry powder and N were weighed and ball milled for 2 h to prepare green bodies, which were then pressed into shape. The dry powder and N were added in a gradient manner, with dry powder to N mass ratios of 9:1, 3:1, and 1:10, respectively, and placed in the lower, middle, and upper layers of the mold for pressing. The pressed green bodies were placed in a muffle furnace and heated to 1280 ℃ at a heating rate of 8 ℃ / min, and held for 1 h, successfully preparing ceramic green bodies with radiative cooling properties.

[0053] Example 4: ① Weigh a certain amount of aluminum acetate and deionized water, adjust the pH to 4 using 20 wt% hydrochloric acid, stir thoroughly at room temperature for 2 h to allow the aluminum acetate to be fully hydrolyzed, and prepare a 0.09 mol / L solution A.

[0054] ② Add a certain amount of glutamic acid to A, stir at room temperature for 6 hours to mix thoroughly, and this mixture is called solution B; ensure that the molar ratio of glutamic acid to Al in solution B is 2:1.

[0055] ③ Weigh a certain amount of sodium tripolyphosphate and deionized water, stir at 80 ℃ for 2 h to fully dissolve them, and prepare a 0.15 mol / L C solution.

[0056] ④ Add a certain amount of lysine to C, stir at room temperature for 6 hours to mix thoroughly, and this is called solution D; ensure that the molar ratio of lysine to sodium tripolyphosphate in solution D is 10:1; mix solutions B and D and stir thoroughly at room temperature for 6 hours to mix thoroughly, and this is called solution E, ensuring that the molar ratio of Al to P in solution E is 1:1.

[0057] ⑤ Transfer E to a hydrothermal reactor (100 ml PTFE liner), place it in an oven and react at 120 °C for 24 h, then cool to room temperature to obtain F; filter F, then wash it three times each with deionized water and ethanol to obtain G; place G in a drying oven and dry at 80 °C for 4 h to obtain H.

[0058] ⑥ Place H in a rotary furnace and heat it to 300 ℃ at a rate of 4 ℃ / min, hold it at that temperature for 0.5 h, then heat it to 1200 ℃ at a rate of 10 ℃ / min, hold it at that temperature for 2 h to obtain I, which is aluminum phosphate.

[0059] ⑦ Weigh 1 g of I and stir it in 30 ml of ethanol for 4 h to obtain solution J; weigh 12 ml of ethanol and 8 ml of deionized water to form an alcohol-water system, and add 4 ml of tetraethyl orthosilicate to it to obtain K.

[0060] ⑧ Slowly add 25 mL of J to 35 mL of K, adjust the pH to 8.5 with 10% ammonia solution, and stir with a magnetic stirrer at 600 r / min for 4 hours at room temperature. This is called L.

[0061] ⑨ Centrifuge L and wash it three times with deionized water and ethanol to obtain M; put M into a drying oven and dry it at 120 °C for 2 h to obtain N, which is SiO2@AlPO4 material.

[0062] In this embodiment, ceramic green bodies were prepared using SiO2@AlPO4 material: 10% montmorillonite, 30% kaolin, 45% talc, 7.5% sodium feldspar, and 7.5% potassium feldspar by mass ratio were weighed and placed in a ball mill jar, and ball milled for 2 hours to prepare a dry powder. A certain amount of the dry powder and nitrogen were weighed and ball milled for 1 hour to form a green body, which was then pressed into shape. The dry powder and nitrogen were added in a gradient manner, with dry powder to nitrogen at mass ratios of 10:1, 1.5:1, and 1:5, respectively, and placed in the lower, middle, and upper layers of a mold for pressing. The pressed green bodies were placed in a muffle furnace and heated to 1300 ℃ at a rate of 10 ℃ / min, and held for 1 hour, successfully preparing a ceramic green body with radiative cooling properties.

[0063] Comparative Example 1: This comparative example only prepared aluminum phosphate (steps ①-⑥), without silica coating (steps ⑦-⑨), and the other preparation methods were the same as in Example 1.

[0064] Comparative Example 2: In this comparative example, commercially available aluminum phosphate was used instead of the aluminum phosphate obtained in steps ①-⑥. Other preparation methods (steps ⑦-⑨) were the same as in Example 1.

[0065] The reflectivity in the solar band and the emissivity in the mid-infrared band of the materials prepared in each embodiment and comparative example were measured, and the results are shown in Table 1: Table 1 Reflectivity and Emissivity of Each Group Table 1 shows that the SiO2@AlPO4 material prepared by the method of this invention has high reflectivity in the solar band and high emissivity in the mid-infrared band, both higher than commercially available aluminum phosphate coated with silica and aluminum phosphate without silica coating. This indicates that the SiO2@AlPO4 material prepared by this invention has excellent cooling performance.

[0066] The materials prepared in Example 1 and Comparative Example 1 were subjected to radiation cooling tests during the day to assess their cooling effect. Figure 3 As shown, from Figure 3 It can be seen that the temperature of the SiO2@AlPO4 material is about 3.5°C lower than that of the AlPO4 material without silica coating, and the temperature of the SiO2@AlPO4 material is 8°C lower than the ambient temperature, indicating that the SiO2@AlPO4 material of the present invention has excellent cooling effect during the day.

[0067] Radiation cooling tests were conducted during the day using ceramic green bodies prepared in Example 1 and original ceramic green bodies without the SiO2@AlPO4 material of this invention. The cooling effect was observed. Figure 4 As shown, from Figure 4It can be seen that the temperature of the ceramic green body containing the SiO2@AlPO4 material of this invention is 3 °C lower than that of the original ceramic green body without this material, and the temperature of the ceramic green body containing the SiO2@AlPO4 material of this invention is about 7.5 °C lower than the ambient temperature. This indicates that the ceramic green body containing the SiO2@AlPO4 material of this invention has excellent cooling effect during the day.

[0068] The ceramic green bodies prepared in Example 1 and Comparative Example 1 were subjected to radiation cooling tests during the day to assess their cooling effect. Figure 4 As shown, from Figure 4 It can be seen that the temperature of the ceramic green body obtained in Example 1 is about 1.5℃ lower than that of the ceramic green body obtained in Comparative Example 1. This indicates that the present invention improves the high temperature resistance of the material by coating aluminum phosphate with silica, so that its structure is not easily damaged after high temperature treatment and can still maintain a good cooling effect.

[0069] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations. The scope of the invention is intended to be defined by the claims and their equivalents.

Claims

1. A method for preparing infrared radiation SiO2@AlPO4 material, characterized in that, Includes the following steps: (1) Preparation of aluminum phosphate; (2) Preparation of SiO2@AlPO4 material: Add aluminum phosphate to ethanol and stir for 2-4 h to obtain solution J, wherein the mass-volume ratio of aluminum phosphate to ethanol is (0.5-1) g: (20-30) mL; add tetraethyl orthosilicate dropwise to alcohol-water system to obtain solution K, wherein the volume ratio of tetraethyl orthosilicate to alcohol-water system is (1-4): (20-50); slowly add solution J to solution K, wherein the volume ratio of solution J to solution K is (20-30): (20-50), adjust pH to 8-10, stir magnetically for 4-6 h, centrifuge, wash, and dry at 80-120 ℃ for 2-8 h to obtain SiO2@AlPO4 material.

2. The method for preparing an infrared radiation SiO2@AlPO4 material according to claim 1, characterized in that, In step (1), the method for preparing aluminum phosphate is as follows: ① Mix aluminum acetate and deionized aluminum, adjust the pH to 4-7, and stir thoroughly at room temperature for 2-4 hours to prepare a 0.03-0.09 mol / L solution A; ② Add glutamic acid to solution A and stir at room temperature for 2-6 hours to obtain solution B; ③ Mix sodium tripolyphosphate and deionized water, and stir at 40~80 ℃ for 2~4 h to prepare a 0.1~0.2 mol / L C solution; ④ Add lysine to solution C and stir at room temperature for 2-6 hours to obtain solution D; mix solution B and solution D and stir thoroughly at room temperature for 4-6 hours to obtain solution E; ⑤ React the E solution at 120~180 ℃ for 12~24 h, cool to room temperature to obtain F; filter and wash the F to obtain G; dry the G at 80~100 ℃ for 2~4 h to obtain H; ⑥ Place the H in a rotary furnace, first heat it to 200-300 ℃ at a rate of 3-5 ℃ / min, hold it at that temperature for 0.5-1 h, then heat it to 700-1200 ℃ at a rate of 5-10 ℃ / min, hold it at that temperature for 2-5 h, and the aluminum phosphate is obtained.

3. The method for preparing an infrared radiation SiO2@AlPO4 material according to claim 2, characterized in that, In step ①, the pH is adjusted using hydrochloric acid with a mass concentration of 10~20wt%.

4. The method for preparing an infrared radiation SiO2@AlPO4 material according to claim 2, characterized in that, In step ②, the molar ratio of glutamic acid to Al in solution B is (1~3):(1~3).

5. The method for preparing an infrared radiation SiO2@AlPO4 material according to claim 2, characterized in that, In step ④, the molar ratio of lysine to sodium tripolyphosphate in solution D is (5~10):(1~3); the molar ratio of Al to P in solution E is (1~1.3):(1~1.3).

6. The method for preparing an infrared radiation SiO2@AlPO4 material according to claim 1, characterized in that, In step (2), the alcohol-water system consists of 5-15 ml of ethanol and 5-15 ml of deionized water.

7. The method for preparing an infrared radiation SiO2@AlPO4 material according to claim 1, characterized in that, In step (2), the pH is adjusted using ammonia water with a volume concentration of 5% to 10%.

8. A SiO2@AlPO4 material prepared by the preparation method according to any one of claims 1 to 7.

9. The application of a SiO2@AlPO4 material prepared by any one of claims 1 to 7 or the SiO2@AlPO4 material as described in claim 8 in the preparation of radiation-cooled ceramics.

10. The application according to claim 9, characterized in that, The radiation-cooled ceramic is prepared by first placing the lower layer material, the middle layer material, and the upper layer material into the lower, middle, and upper layers of the mold respectively, and then pressing them into shape. The pressed blank is then placed in a muffle furnace and heated to 1200~1300 ℃ at a rate of 5-10 ℃ / min and held for 1~2 h to obtain the radiation-cooled ceramic. The mass ratio of the dry powder to the SiO2@AlPO4 material in the lower layer is (9~11):1; The mass ratio of the dry powder in the intermediate layer to the SiO2@AlPO4 material is (1~3):1; The mass ratio of the dry powder to the SiO2@AlPO4 material in the upper layer is (1~3):10; The dry powder is prepared by: placing 10-20% montmorillonite, 20-30% kaolinite, 30-50% talc, 5-15% sodium feldspar, and 5-15% potassium feldspar into a ball mill jar and ball milling for 1-2 hours to obtain the dry powder.

Citation Information

Patent Citations

  • Silicon dioxide coated magnesium phosphite radiation refrigeration material and preparation method thereof

    CN111394069A